2003
DOI: 10.1128/aac.47.8.2669-2673.2003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biochemical Characterization of a Novel Class A β-Lactamase (HER-1) from Escherichia hermannii

Abstract: Escherichia hermannii showed a low level of resistance to amoxicillin and ticarcillin, reversed by clavulanate, and a moderate susceptibility to piperacillin but was susceptible to all cephalosporins. A bla gene was cloned and encoded a typical class A ␤-lactamase (HER-1, pI 7.5), which shares 45, 44, 41, and 40% amino acid identity with other ␤-lactamases, AER-1 from Aeromonas hydrophila, MAL-1/Cko-1 from Citrobacter koseri, and TEM-1 and LEN-1, respectively. No ampR gene was detected. Only penicillins were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The in vitro susceptibilities of these isolates showed that piperacillin-tazobactam, ceftazidime, cefazolin, cefixime, aztreonam, gentamicin, tobramycin imipenem, meropenem, and amikacin were active in vitro . Isolates also showed a low-level resistance against amoxicillin, similar to that reported by Fitoussi et al and Beauchef-Havard et al ( 9 , 10 ). However, more clinical experiments are mandatory.…”
Section: Discussionsupporting
confidence: 87%
“…The in vitro susceptibilities of these isolates showed that piperacillin-tazobactam, ceftazidime, cefazolin, cefixime, aztreonam, gentamicin, tobramycin imipenem, meropenem, and amikacin were active in vitro . Isolates also showed a low-level resistance against amoxicillin, similar to that reported by Fitoussi et al and Beauchef-Havard et al ( 9 , 10 ). However, more clinical experiments are mandatory.…”
Section: Discussionsupporting
confidence: 87%
“…However, biofilm formation and its potential role in infections with E. hermannii still have to be confirmed in other studies. Furthermore, E. hermannii has a natural resistance to penicillin, ampicillin, and carbenicillin because of its β-lactamase production - which complicates treatment [ 10 ]. Currently, there is insufficient clinical data on the optimal antibiotic treatment - but mostly various β-lactams and quinolones with in vivo susceptibility have been used.…”
Section: Resultsmentioning
confidence: 99%
“…Both strains BP-1(T) and BP-2 are multidrug resistant Enterobacteriaceae which harbor extended spectrum β-lactamases and are therefore classified as a serious antimicrobial threat by the CDC (CDC, 2013 ; Iredell et al, 2016 ). The Class A β-lactamase identified by Resfams had high identity to bla HER family genes, which were previously described in Atlantibacter hermanii but only conferred resistance to penicillins (Beauchef-Havard et al, 2003 ). As this gene was proximal to a tetR response regulator, it is possible that it may be inducible, like the ampR/ampC system widespread in Enterobacter and Citrobacter (Vadlamani et al, 2015 ).…”
Section: Discussionmentioning
confidence: 81%